The Effect of Product Quality on Customer Loyalty Toward Second Original Shoes, Mediated by Customer Satisfaction and Trust at Flshoes Collection - Yudha Pratama Werokati; Elimawaty Rombe; Asriadi (JURNAL MANAJEMEN MOTIVASI, 2026)
This study examines the effect of product quality on customer loyalty toward second original shoes at Flshoes Collection, with customer satisfaction and trust as mediating variables. Using a quantitative approach, the findings reveal that product quality has a positive and significant impact on customer loyalty. Satisfaction and trust significantly mediate this relationship, strengthening the effect of product quality on loyalty. The results highlight the importance of transparent and consistent communication in building customer trust and fostering long-term loyalty. Flshoes Collection is therefore encouraged to continuously improve product quality and service to remain competitive and enhance overall customer experience